O Przekształceniach Ustroju Czterowęzłowego przez Wymianę Prętów - Grycz, J. (Engineering Transactions, 1960)
An arbitrary four-node isostatic field of plane lattice is considered. The object of the paper is to determine such a system of bars for a pre- scribed load and an invariable configuration of the nodes, that the elastic potential takes its minimum value. The paper contains theorems on the existence of four-node structures gathering the minimum value of the elastic potential. In addition, it gives the derivation of the relations for determining the minimum value structure. The considerations concerning the four-node lattice field constitute a basis for the analysis of the minimum value of the potential of an arbitrary isostatic plane lattice with transformations by exchanging bars.